PENERAPAN METODE GASING DALAM MENINGKATKAN KEMAMPUAN BERHITUNG SISWA DI KELAS VI MIN 1 LOMBOK BARAT - Hidayatil Qur’ani; Siska Ayu Safitri; M. Talal Hikam; Djuita Hidayati (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine students' numeracy ability through the toping method (easy, fun, and fun). The subject of this study is grade VI students of MIN 1 Lombok Barat, which totals 26 students consisting of 12 boys and 14 girls. In the process of generating data, the researcher uses a qualitative research method that is described descriptively. The data collection techniques in this study were obtained through observation, interviews and documentation. From the data obtained, the average student has not been able to calculate the basics (addition, subtraction, multiplication and division), has not memorized multiplication so that it affects the student's grade. Before the teacher applied the toping method, there were 10 students whose scores were below 70 and after applying the toping method, there was an increase in student scores.